2020
DOI: 10.1212/wnl.0000000000009632
|View full text |Cite
|
Sign up to set email alerts
|

Keeping people with epilepsy safe during the COVID-19 pandemic

Abstract: ObjectivesTo provide information on the effect of the coronavirus disease of 2019 (COVID-19) pandemic on people with epilepsy and provide consensus recommendations on how to provide the best possible care for people with epilepsy while avoiding visits to urgent care facilities and hospitalizations during the novel coronavirus pandemic. MethodsThe authors developed consensus statements in 2 sections. The first was "How should we/ clinicians modify our clinical care pathway for people with epilepsy during the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
148
2
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(173 citation statements)
references
References 16 publications
5
148
2
18
Order By: Relevance
“…19,20 The feasibility of telehealth in epilepsy care, including delivery of complex care to patients with refractory epilepsy, has similarly been demonstrated, with comparable outcome and high patient satisfaction. 13,[21][22][23] The lack of commensurate reimbursement has historically been the barrier to greater adoption. 24 Several early studies have examined the effect of transition to telehealth during the COVID-19 pandemic.…”
Section: Telehealthmentioning
confidence: 99%
“…19,20 The feasibility of telehealth in epilepsy care, including delivery of complex care to patients with refractory epilepsy, has similarly been demonstrated, with comparable outcome and high patient satisfaction. 13,[21][22][23] The lack of commensurate reimbursement has historically been the barrier to greater adoption. 24 Several early studies have examined the effect of transition to telehealth during the COVID-19 pandemic.…”
Section: Telehealthmentioning
confidence: 99%
“…38 As recently summarized by an international group of epileptologists, no case or study has been reported yet to justify any direct relation between the potentiation of epileptic seizures and COVID-19. 14 In this context, it also needs to be taken into consideration that seizure onset during an infection can also be only a coincidence, considering the extreme ratio between reported COVID-19 cases with seizures and the overall number of reported COVID-19 cases, as well as that epilepsy is a neurological disease with a high prevalence. This might apply to at least some of the cases that have been reported.…”
Section: Box 1 Search Strategy Profile Of the Reviewmentioning
confidence: 99%
“…In addition, a group of international clinical experts published consensus statements on the impact of the COVID-19 pandemic on patients with epilepsy. 14 Although it is evident from the very low number of reported cases with more severe neurological manifestations that COVID-19-associated neurological disease seems to be a very rare event affecting only a small subgroup of patients, it is nevertheless of interest to review the characteristics of available cases. In this context, we will discuss proven and potential mechanisms, by which an infection with respiratory viruses and with SARS-CoV-2 in particular may affect seizure thresholds.…”
mentioning
confidence: 99%
“…Patients have also been advised to avoid emergency room visits unless for life-threatening conditions. Different concerns regarding epilepsy and COVID-19 have been raised, yet current evidence suggests that PWE are not more likely to become infected with the virus and nor are they at higher risk of complications [6,7]. The concern, however, is that seizures may result in emergency room or clinical visits, and so better control of seizures is required.…”
Section: Introductionmentioning
confidence: 99%